In Search of Lost Revenue : Why Restoring Fiscal Soundness After a Crisis is Harder Than it Looks - Miyazaki, Masato (Washington, D.C. : International Monetary Fund, 2010)
This note argues that because fiscal deficit after a crisis owe much to a drop in tax revenues and a sluggish revenue growth, its adjustment has to rely more on revenue augmentation than commonly thought. Cutting extra spending in the wake of the crisis would not balance the book, while a natural growth of tax revenue after the recovery may take a long time before financing the pre-crisis level of expenditure. Faced with unpopular choices, the government may implicitly prefer seeing higher inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet